Development of TaqMan-Based Real-Time qPCR Method for Accurate Detection and Quantification of Citrus Psorosis Virus and Cytoplasmic-Type Citrus Leprosis Virus in Saplings - Minhue Jung; Na Hee Kim; Seung Hyeon Oh; Kook-Hyung Kim (The Plant Pathology Journal)
In 2022, citrus fruits were the second most widely produced fruit globally, highlighting their significant role in the fruit industry. However, due to their clonal propagation, these fruits are highly susceptible to viral infections, posing challenges for growers. In response to the booming nursery market, the Korean plant quarantine station reported over 80 million sapling stocks, with 15% being discarded after rigorous inspection due to contamination or disease. As the global nursery trade continues to expand, there is an urgent need for a fast and accurate diagnostic tool to ensure the health of plant stocks. In this study, we developed a TaqMan-based real-time reverse transcription-quantitative PCR assay specifically designed to detect two critical citrus viruses: citrus psorosis virus and citrus leprosis virus C. Our assay demonstrated the capability to detect virus sequences with as few as 30 copies, maintaining high PCR efficiency with RNA extracted from both twig and leaf tissues. Additionally, we incorporated an artificial sequence into the positive controls, which effectively served as a marker for detecting potential sample contamination. This comprehensive diagnostic system promises to enhance plant quarantine measures and phytosanitation practices, providing a reliable and efficient solution to safeguard citrus crops from viral threats.